Post-18 Education and Funding in England - Callender, Claire (International Higher Education, 2019)
In May 2019, the government-commissioned report on Post-18 Education and Funding in England was published. Here we outline the report’s main recommendations for both higher and further education funding, which seek to tackle the disparity between the 50 percent of young people who participate in higher education and the other 50 percent who do not.